Akuntansi dan Efektivitas Pemungutan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) dan Kontribusinya terhadap Pendapatan Daerah Di Kota Semarang Periode Tahun 2008-2011 - Muhamad Fauzan; Didik Ardiyanto (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the effectiveness of the accounting and collection of customs acquisitionof land and buildings (BPHTB) and its contribution to regional income in the city of Semarangperiod 2008-2011. The effectiveness of tax revenue can be an indicator of performance in theDepartment of Revenue (Dipenda) Semarang. Tax revenues have been called effective ifacceptance in accordance with a predetermined potential. The purpose of this research is to gainknowledge of the effectiveness and contribution to the collection of customs acquisition of land andbuildings based on the target and the realization of the revenue in the city of Semarang. The dataused in this research is the realization of the target data and reports BPHTB from 2008-2010obtained from the Office of Tax Semarang and BPHTB reports in 2011 and reported revenue ofSemarang are dipeoleh years 2008-2011 from the Department of Finance and Asset ManagementDistrict (DPKAD) Semarang City Government. The data analysis techniques with descriptivequantitative methods to analyze the data. The results showed that (1) the effectiveness of revenue in2008-2011 experienced BPHTB kondusi fluctuating with an average revenue of 108% which isincluded in the criteria is very effective. (2) the rate of growth in the city of Semarang BPHTB theyears 2009-2011 average of 9.17% which is included in the criteria is very less. (3) contribution toregional income BPHTB average 6.81% were included into criteria lacking, contribute to the fundbalance BPHTB average of 10.96% which is included in the criteria less, BPHTB contribution toPAD with an average of 45, 41% included in the criteria of good and contribute to the local taxBPHTB with an average of 52.52% included in the excellent category.